2020
DOI: 10.1101/2020.09.29.319707
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Architecture of the Tuberous Sclerosis Protein Complex

Abstract: The Tuberous Sclerosis Complex (TSC) protein complex (TSCC), comprising of three subunits TSC1, TSC2, and TBC1D7, is widely recognised as a key integration hub for cell growth and intracellular stress signals upstream of the mammalian target of rapamycin complex 1 (mTORC1). The TSCC negatively regulates mTORC1 by acting as a GTPase-activating protein (GAP) towards the small GTPase Rheb. Both human TSC1 and TSC2 are important tumor suppressors, and their mutations underlie the tuberous sclerosis disease. We us… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
6
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(10 citation statements)
references
References 31 publications
4
6
0
Order By: Relevance
“…Consistent with results from two other groups[7,8], we detected ∼10 × 40 nm highly flexible particles in NSEM analysis of human recombinant pTSC overexpressed under the control of CMV promoters in human cells (Fig. 1).…”
Section: Resultssupporting
confidence: 91%
See 4 more Smart Citations
“…Consistent with results from two other groups[7,8], we detected ∼10 × 40 nm highly flexible particles in NSEM analysis of human recombinant pTSC overexpressed under the control of CMV promoters in human cells (Fig. 1).…”
Section: Resultssupporting
confidence: 91%
“…We found that recombinant human pTSC co-purifies with heat shock protein 70 (Hsp70), as observed in other studies[7,13]. However, no density could be found for the heat shock protein in the recent cryoEM maps indicating that the heat shock proteins most likely binds misassembled or partially unfolded pTSC.…”
Section: Resultssupporting
confidence: 81%
See 3 more Smart Citations